2018
DOI: 10.1101/415331
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Systematic analysis of theMyxococcus xanthusdevelopmental gene regulatory network supports posttranslational regulation of FruA by C-signaling

Abstract: 25Upon starvation Myxococcus xanthus undergoes multicellular development. Rod-shaped cells move 26 into mounds in which some cells differentiate into spores. Cells begin committing to sporulation at 24-27 30 h poststarvation, but the mechanisms governing commitment are unknown. FruA and MrpC are 28 transcription factors that are necessary for commitment. They bind cooperatively to promoter regions 29 and activate developmental gene transcription, including that of the dev operon. Leading up to and 30 during… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 70 publications
0
8
0
Order By: Relevance
“…A rising level of FruA* produced in response to C-signaling during development would not only promote mound formation, it would trigger gene expression and lead to sporulation (56)(57)(58). FruA* and MrpC have been proposed to bind cooperatively to activate the transcription of genes that commit rod-shaped cells to form spores (5,28,35) (Fig. 1).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…A rising level of FruA* produced in response to C-signaling during development would not only promote mound formation, it would trigger gene expression and lead to sporulation (56)(57)(58). FruA* and MrpC have been proposed to bind cooperatively to activate the transcription of genes that commit rod-shaped cells to form spores (5,28,35) (Fig. 1).…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, or in addition, MrpC itself could be a nutrient-sensing autorepressor. In two recent studies, MrpC was shown to negatively autoregulate (5,62), and it may do so by competing with MrpB-P for overlapping binding sites in the mrpC promoter region (62). It is also possible that CTTYE addition destabilizes mrpC transcripts.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations